Identyfikacja różnic w poziomie zdolności szybkościowych i wytrzymałościowo szybkościowych na przykładzie zawodników drugoligowego zespołu piłki nożnej = The identification of the differences in the level of the speed abilities and the endurance-speed abilities: a case study from the second league football team - Różycki, Waldemar (Journal of Education, Health and Sport, 2015)
Różycki Waldemar. Identyfikacja różnic w poziomie zdolności szybkościowych i wytrzymałościowo szybkościowych na przykładzie zawodników drugoligowego zespołu piłki nożnej = The identification of the differences in the level of the speed abilities and the endurance-speed abilities: a case study from the second league football team. Journal of Education, Health and Sport. 2015;5(11):639-649. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35713 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A639-649 http://pbn.nauka.gov.pl/works/684946 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Różycki Waldemar. Identyfikacja różnic w poziomie zdolności szybkościowych i wytrzymałościowo szybkościowych na przykładzie zawodników drugoligowego zespołu piłki nożnej. Quality in Sport. 2015;1(2):17-25. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Waldemar Różycki[1] Politechnika Częstochowska, Studium Wychowania Fizycznego i Sportu Identyfikacja różnic w poziomie zdolności szybkościowych i wytrzymałościowo szybkościowych na przykładzie zawodników drugoligowego zespołu piłki nożnej The identification of the differences in the level of the speed abilities and the endurance-speed abilities: a case study from the second league football team Streszczenie Wykorzystanie umiejętności techniczno – taktycznych w dużej mierze uzależnione jest od kondycyjnego przygotowania zawodnika. W celu uzyskania informacji na temat zdolności zawodników do wykonywania zadań lokomocyjnych przeprowadza się szereg prób i testów. Celem pracy było zidentyfikowanie różnic w poziomie zdolności szybkościowych i wytrzymałościowo szybkościowych zawodników drugoligowego klubu piłkarskiego na podstawie testu wielokrotnych wysiłków o maksymalnej intensywności z krótkotrwałymi przerwami o charakterze aktywnym (zmodyfikowany test Rast). Parametry poddane analizie to: szybkość startowa, szybkość biegowa, wytrzymałość szybkościowa 1, wytrzymałość szybkościowa 2. Analiza materiału badawczego dowiodła, że badana grupa istotnie różni się pod względem zdolności do wykonywania zadań lokomocyjnych. Najwyższy poziom różnic stwierdzono w parametrze szybkość startowa, poziom najniższy w parametrze wytrzymałość szybkościowa 1. Analiza skupień okazała się skuteczną metodą w procesie identyfikacji względnie jednorodnych grup zawodników. Słowa kluczowe: piłka nożna. zdolności kondycyjne, analiza skupień. Abstract The use of technical-tactical abilities is to a great extent dependent on the condition preparation of the player. In order to obtain the information on the players abilities to perform locomotive tasks a collection of tests and trials is carried out. The aim of the work was to identify the differences in the level of speed abilities and endurance-speed abilities of the players of the second league football club basing on a test including multiple effort tasks of maximum intensity with short-term breaks of the active character (modified Rast Test). The analyzed parameters included: start speed, run speed, speed endurance 1, speed endurance 2. The analysis of the research data has proved that the group varies in the abilities to perform locomotive tasks. The highest level of differences was detected in the parameter of start speed, the lowest in speed endurance 1. The cluster analysis appeared to be a sufficient method of identification of relatively homogenous groups of players. Key words: football, condition abilities, cluster analysis. [1] e-mail: waldemarrozycki@op.pl, tel: 608 149 380